THE USE OF INTERACTIVE TECHNOLOGIES IN RUSSIAN LANGUAGE LESSONS - Kholmurotova Safiya Kuldashevna (Bright Mind Publishing, 2025)
This article examines the role and effectiveness of interactive technologies in teaching the Russian language. It highlights modern pedagogical approaches that enhance students’ motivation, communicative competence, and active participation in the learning process. The use of digital tools, interactive methods, and multimedia resources is analyzed as a means of developing language skills, critical thinking, and collaborative learning. Special attention is given to the practical application of interactive technologies in classroom activities and their impact on improving the quality of language education.
Keywords: Interactive technologies, Russian language teaching, modern pedagogy, digital tools, student engagement, communicative competence, innovative methods.